2021
DOI: 10.1248/bpb.b21-00253
|View full text |Cite
|
Sign up to set email alerts
|

Structural Insights into the Loss-of-Function R288H Mutant of Human PPARγ

Abstract: Peroxisome proliferator-activated receptor gamma (PPARγ) is a nuclear receptor and the molecular target of thiazolidinedione-class antidiabetic drugs. It has been reported that the loss of function R288H mutation in the human PPARγ ligand-binding domain (LBD) may be associated with the onset of colon cancer. A previous in vitro study showed that this mutation dampens 15-deoxy-Δ 12,14 -prostaglandin J2 (15d-PGJ2, a natural PPARγ agonist)-dependent transcriptional activation; however, it is poorly understood why… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Of note is also that of these patients, 83% also had diabetic kidney disease [15]. Another study demonstrated that loss of function mutation of arginine 288 to histidine in the ligand-binding domain (LBD) resulted in significant conformational changes in the protein that lead to blunting of the activation via prostaglandins [16].…”
Section: Introductionmentioning
confidence: 99%
“…Of note is also that of these patients, 83% also had diabetic kidney disease [15]. Another study demonstrated that loss of function mutation of arginine 288 to histidine in the ligand-binding domain (LBD) resulted in significant conformational changes in the protein that lead to blunting of the activation via prostaglandins [16].…”
Section: Introductionmentioning
confidence: 99%